2000
DOI: 10.4141/a99-039
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the growth performance and carcass characteristics of lambs produced in Quebec

Abstract: Hammell, K. L. and Laforest, J. P. 2000. Evaluation of the growth performance and carcass characteristics of lambs produced in Quebec. Can. J. Anim. Sci. 80: 25-33. Data for a total of approximately 1100 lambs tested in 12 trials from 1992 to 1995 in commercial lamb test stations in Quebec were used to determine the effect of sex, sire breed and genetic type on growth performance and carcass characteristics. Lambs were housed two to a pen and fed commercial diets. Maximum test length was 112 d. Lambs were slau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 11 publications
(12 reference statements)
3
1
0
2
Order By: Relevance
“…With the exception of DG 1, higher daily gains were found in males in all cases. Similar findings were reported by Hammel and Laforest (2000), Dixit et al (2001), Fernandes et al (2001), Macit et al (2001), Abegaz et al (2002), and Matika et al (2003). However, it is necessary to state that the above-mentioned authors recorded higher daily gains in males in all intervals under study.…”
Section: Resultssupporting
confidence: 86%
“…With the exception of DG 1, higher daily gains were found in males in all cases. Similar findings were reported by Hammel and Laforest (2000), Dixit et al (2001), Fernandes et al (2001), Macit et al (2001), Abegaz et al (2002), and Matika et al (2003). However, it is necessary to state that the above-mentioned authors recorded higher daily gains in males in all intervals under study.…”
Section: Resultssupporting
confidence: 86%
“…Although not significant, Suffolk lambs had higher corrected cold killing-out proportion. Our results seems to confirm the theory that meat breeds tend to have smaller killing-out proportions than dam breeds (Hammell & Laforest, 2000;Wood, MacFie, & Brown, 1983;Wylie, Chestnutt, & Kilpatrick, 1997), since CGB breed presents dam breed characteristics (Teixeira et al, 1996). The degree of maturity had no effect (P > 0.05) on killing-out proportions.…”
Section: Killing-out Proportionsupporting
confidence: 78%
“…Faster growth (Table 4) was partly associated with higher LW at birth and the influence of sex hormones on growth rate of lambs (Selaive-Villarroel et al, 2008). Faster growth requires more nutrients and actually Hammell and Laforest (1999) found that male lambs consumed more dry feed than females and according to several authors (Butterfield, 1988;Santos et al, 2008) the higher content of fat in the body of the female lambs causes a lower growth rate, compared with the leaner males.…”
Section: Discussionmentioning
confidence: 94%